JENIS-JENIS CRUSTACEA DI CAGAR ALAM TELUK KLOWE PULAU ENGGANO KABUPATEN BENGKULU UTARA - Duya, Novia; Noveria, Rista (Universitas Bengkulu, 2019)
Mangrove forest in Cagar Alam of Klowe Bay is one of the conservation forest on Enggano Island. Mangroves for serving as an ecological function that can keep from coastal abrasion. Mangroves can also be used as a habitat for water biota, one of which is crustaceans. The aim of this research is identification the types of Crustaceans in Klowe Bay Cagar Alam, Kahyapu Village, Enggano Island, North Bengkulu Regency. This research was conducted in January 2018 with exploration methods and the data were analyzed by descriptive qualitative. Based on theresults of the study, obtained 13 species, with the most genera found in Uca. The species found consist of Coenobita violascens, Uca annulipes, Uca boninensis, Uca crassipes, Uca dussumeiri, Uca tetragonon, Uca